2006
DOI: 10.1128/jcm.44.1.102-107.2006
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology ofKlebsiella pneumoniaein an Australian Tertiary Hospital and Its Implications for Vaccine Development

Abstract: The aim of this study was to determine the diversity of Klebsiella pneumoniae capsular serotypes in an Australian setting. Consecutive (n ‫؍‬ 293) nonrepetitive isolates of K. pneumoniae from a large teaching hospital laboratory were analyzed. The majority of isolates were from urinary specimens (60.8%); the next most common source was sputum (14.3%), followed by blood (14%). Serotyping revealed a wide range of capsule types. K54 (17.1%), K28 (4.1%), and K17 (3.1%) were the most common, and K54 isolates displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 31 publications
2
64
0
1
Order By: Relevance
“…A previous survey from Australia on the serotypes of 293 K. pneumoniae isolates (13) reported that 88 isolates (30%) were nontypeable by countercurrent immunoelectrophoresis (27), while 54 had a positive reaction for more than one serotype. Likewise, we had similar difficulties in serotyping using double immunodiffusion (26), as this study revealed.…”
Section: Discussionmentioning
confidence: 99%
“…A previous survey from Australia on the serotypes of 293 K. pneumoniae isolates (13) reported that 88 isolates (30%) were nontypeable by countercurrent immunoelectrophoresis (27), while 54 had a positive reaction for more than one serotype. Likewise, we had similar difficulties in serotyping using double immunodiffusion (26), as this study revealed.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties in determining capsular types in Klebsiella by serological diagnosis have been noted in several studies (36)(37)(38). Consequently, several techniques for molecular capsular typing were developed to circumvent these problems (7,9,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial strains and plasmids used in this study are listed in Table S1 in the supplemental material. K. pneumoniae AJ218 is a human urinary tract infection isolate (27). Unless otherwise stated, all bacterial strains were cultured at 37°C, with shaking, in Luria-Bertani (LB) broth overnight.…”
Section: Methodsmentioning
confidence: 99%